2010
DOI: 10.1029/2009jb006289
|View full text |Cite
|
Sign up to set email alerts
|

Deformation processes adjacent to active faults: Examples from eastern California

Abstract: [1] Major seismogenic faults are embedded within narrow zones of inelastic off-fault deformation (OFD), where both distributed displacement and modification of rock properties occur. Active distributed displacement may affect slip rate estimates, seismic energy radiation and geodynamic models. This study addresses the role of OFD in the displacement history and mechanical behavior of seismogenic faults, by multisite study of deformed geologic features adjacent to 30-60 km long active strike-slip faults of <10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 86 publications
0
64
0
Order By: Relevance
“…We impose the damage zone to have different widths (W) ranging from ∼3 to 50% of the fault length. It is important to note that, although it has long been supposed that damage was confined only within a very narrow zone around the faults [ Li et al ., ; Ben‐Zion et al ., ; Fialko , ; Fielding et al ., ; Mitchell and Faulkner , ], an increasing number of observations suggests that it might rather extend over large areas up to several kilometers [ Spudich and Olsen , ; Manighetti et al ., ; Oskin et al ., ; Cochran et al ., ; Barbot et al ., ; Shelef and Oskin , ; Griffith et al ., ; Smith et al ., ]. Several studies have suggested that the damage zone width might scale linearly with the fault length and/or displacement [ Scholz et al ., ; Knott et al ., ; Vermilye and Scholz , ; Beach et al ., ; Manighetti et al ., ; Savage and Brodsky , ], but the actual ratios between damage zone width and fault length are still poorly known.…”
Section: Model Resultsmentioning
confidence: 99%
“…We impose the damage zone to have different widths (W) ranging from ∼3 to 50% of the fault length. It is important to note that, although it has long been supposed that damage was confined only within a very narrow zone around the faults [ Li et al ., ; Ben‐Zion et al ., ; Fialko , ; Fielding et al ., ; Mitchell and Faulkner , ], an increasing number of observations suggests that it might rather extend over large areas up to several kilometers [ Spudich and Olsen , ; Manighetti et al ., ; Oskin et al ., ; Cochran et al ., ; Barbot et al ., ; Shelef and Oskin , ; Griffith et al ., ; Smith et al ., ]. Several studies have suggested that the damage zone width might scale linearly with the fault length and/or displacement [ Scholz et al ., ; Knott et al ., ; Vermilye and Scholz , ; Beach et al ., ; Manighetti et al ., ; Savage and Brodsky , ], but the actual ratios between damage zone width and fault length are still poorly known.…”
Section: Model Resultsmentioning
confidence: 99%
“…Overall, our comparison of strain localization with surface material type strongly suggests that, given sufficiently thick sediments, there is a correlation between percent OFD and material type, as suggested by models [e.g., Ma , ; Ma and Andrews , ; Kaneko and Fialko , ] and field observations [e.g., Treiman et al ., ; Shelef and Oskin , ; Van Dissen et al ., ; Oskin et al ., ; Duffy et al ., ; Dolan and Haravitch , ]. The precise degree of influence that near‐surface material properties and thickness have on strain localization provides fertile ground for future research, and many more observations such as those detailed above from other specific ruptures are needed.…”
Section: Discussionmentioning
confidence: 98%
“…The near‐fault regions that deformed inelastically in the 2016 earthquake likely spatially overlap with the compliant fault damage zone created by many past ~ M 7 earthquakes on the FHFZ. Future imagery differencing at still‐higher spatial resolution may facilitate examining whether the fault zone is best described as a block model with decreasing block dimension and material rigidity toward the principal fault (e.g., Shelef & Oskin, ) or as a broad shear belt with areas of localized deformation (e.g., Johnson et al, ).…”
Section: Discussionmentioning
confidence: 99%